Gamma glutamyl transferase - an underestimated marker for cardiovascular disease and the metabolic syndrome - Manuela G Neuman; Stephen Malnick; Lucy Chertin (Frontiers Media S.A., 2020)
Gamma glutamyl transferase (GGT) is an enzyme in glutathione and cysteine metabolism. GGT is a standard liver enzyme test reflecting biliary tract involvement. It also has a prooxoidant activity and a modulating influence on endothelia dysfunction. GGT is associated with the metabolic syndrome and is often elevated in patients with NAFLD. There is also a role for GGT activity in several aspects cardiovascular disease. There is an association between elevated GGT and cardiovascular mortality, atrial fibrillation, exacerbation of congestive heart failure . In addition there is an association with obstructive sleep apnea. We review the evidence available and suggest that there is a need for further assessing the use of GGT, together with the presence of the metabolic syndrome as a prognostic marker.